Quality of Life in University Students with Diabetes Distress: Type 1 and Type 2 of Diabetes Differences - Samah A. Moawd (Journal of Diabetes Research)
Background. This study constitutes a preliminary trial to clarify the relationship between quality of life (QoL) and diabetes distress (DD in patients with diabetes mellitus (DM) by comparing patients with type 1 and type 2 diabetes. Methods. A cross-sectional study of university students with diabetes (type 1 and type 2) diabetes. One hundred sixty-six students were assigned to participate in this study. A self-report questionnaire on demographic and clinical parameters was taken. Rating worries and anxieties related to diabetes were evaluated using the diabetes distress scale-17, and quality of life was tested using SF-36 v2. Results. No significant differences were observed in the level of DD according to sociodemographics in type 1 DM (T1DM) and type 2 DM (T2DM) (p>0.05). The mean scores for Physical Component Summary (PCS) and Mental Component Summary (MCS) and six subscales of the SF-36 v2 demonstrated no significant differences between T1DM and T2DM (p>0.05). High scores of diabetes distress were independently associated with lower glycemic control for students with both types of diabetes. Likewise, high scores of distress were associated with lower PCS (p<0.05). Additionally, the results showed that high scores of diabetes distress were associated with lower MCS (p<0.05). Conclusions. University students with diabetes showed a high level of DD with no significant differences between both types of diabetes; this consequently affects all components of QoL. Psychological support is the better choice for those students for better health and future career.